Analysis and Design of PLL Motor Speed Control System - Qi Chao Zhang (Institute of Advanced Engineering and Science, 2013)
Phase-locked technology in motor speed control system has a wide range of applications, Especially for high accuracy in the motor steady speed operation situation, more and more use of phase-locked servo control system. This paper describes the block diagram and mathematical model of phase-locked control system, Shows the circuit parameter calculation method This and combined with design example analysis of phase-locked control system, Indicated through the theory and practice, using PLL can obtain good speed control precision. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3391